2022
DOI: 10.3389/fenvs.2022.1019499
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable corporate environmental information disclosure: Evidence for green recovery from polluting firms of China

Abstract: For a greener society, good corporate environmental information disclosure is crucial. This study empirically examines the influence of media attention and state-owned equity, and their interaction on corporate environmental information disclosure by A-share heavily polluting firms in the Shanghai and Shenzhen stock markets from 2015 to 2019. The results show that state-owned equity can improve the level of corporate environmental information disclosure; however, it mainly affects financial environmental infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…The state’s regression coefficient was 0.124 at the 1% level of statistical significance. This confirms hypothesis H 1 , and this finding is consistent with the results of Long et al [ 14 ] who verified the effect of state-owned equity on corporate EID, but the difference is that this study tests the state-owned equity involved in private firms, and it shows that mixed equity structure still promotes EID in private firms. Column (3) tests the moderating impact of media attention on state capital participation and EID; state and media had a 0.042 interaction term coefficient, which was significant at the 5% level, indicating support for hypothesis H 2 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The state’s regression coefficient was 0.124 at the 1% level of statistical significance. This confirms hypothesis H 1 , and this finding is consistent with the results of Long et al [ 14 ] who verified the effect of state-owned equity on corporate EID, but the difference is that this study tests the state-owned equity involved in private firms, and it shows that mixed equity structure still promotes EID in private firms. Column (3) tests the moderating impact of media attention on state capital participation and EID; state and media had a 0.042 interaction term coefficient, which was significant at the 5% level, indicating support for hypothesis H 2 .…”
Section: Resultssupporting
confidence: 92%
“…Few scholars have studied the impact of equity structure on corporate EID. Moreover, previous research on the equity structure of enterprises has predominantly focused on a single dimension of state-owned and non-state-owned equity [ 13 , 14 ]. This article examines the level of EID in private enterprises under mixed equity in the Chinese context, demonstrating that mixed equity can effectively integrate resources and improve governance mechanisms, thereby altering the EID decisions of enterprises, and to some extent, enriching literature research on enterprise environmental information disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…A munkáltatói márka leginkább a versenytársaktól való megkülönböztetésben érezteti jelentőségét (Backhaus-Tikoo, 2004) és olyan -külső és belső -szereplőket foglal magában, akik a szervezetet "kiváló munkahelynek" tekintik (McLeod-Waldman, 2011). A 2010-es évekre a munkáltatói márkaépítés a szervezetek fenntarthatósági stratégiájának szerves részének tekinthető: olyan új munkáltatói márkaépítési ötletek, utak születtek, amelyek a márkaépítés, a humánerőforrás-menedzsment és a CSR elméleteit holisztikus és folyamatalapú diszciplínaként értelmezték újra (Kryger Aggerholm et al, 2011;Long et al, 2022). A társadalmi identitás-elméletre és a jelzéselméletre támaszkodva azt feltételezték, hogy a cégek felhasználhatják vállalati társadalmi teljesítmény (CSPcorporate social performance) tevékenységeiket álláspályázók vonzására (Greenig-Turban, 2000).…”
Section: Irodalmi áTtekintésunclassified
“…It should be noted that managers of socially responsible companies are motivated not only to use earnings management to increase or decrease profits but also to manipulate the information they disclose in order to gain personal benefits. Although a non-significant relationship was found between environmental disclosure and the use of earnings management, managers of large companies are more likely to disclose environmental information when they are under greater external pressure (Sun et al, 2010;Long et al, 2022). Kolsi & Attayah (2018), who studied the performance of socially responsible companies, found that companies use earnings management to smooth out fluctuations in profits.…”
Section: Literature Reviewmentioning
confidence: 99%